Q-switching in an erbium-doped fibre laser using a saturable absorber based on vanadium pentoxide polyethylene glycol in the long-wavelength range - Baharom, Mohamad Faizal; Ab Rahman, Mohd Fauzi; Abdul Latiff, Anas; Ahmad, Aminah; Jali, Mohd Hafiz; Wadi Harun, Sulaiman (Wydawnictwo SIGMA-NOT, 2024)
The laser generation was produced at a wavelength of 1562.4 nm with a small spectral bandwidth of 0.4 nm using a short-pulse erbium-doped fibre laser with unique group delay dispersion. This process was generated by Q-switching, which was accomplished using a vanadium oxide polyethylene glycol (V2O5-PEG) film saturable absorber (SA) within an all-fiber ring cavity arrangement. The laser generated a peak output power of 0.4 mW, a maximum pulse energy of 3.2 nJ, and an astonishingly brief pulse width of 4.7 s. These results highlight the possibility of the V2O5 film as a workable SA substitute for producing pulsed lasers.